Estimates of the solutions to the equations of motion for viscous fluid in a moving cavity with a porous damper - Sudakov, S. N. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Estimates for $L_2$-norms of solutions of equations of motion for viscous fluid in a moving elliptic cavity with a porous damper are obtained.